Raising trans kids : what to expect when you weren't expecting this - Minor, Rebecca, LICSW (100 Block By Row House, an imprint of Row House Publishing, Inc., 2025)
"Raising Trans Kids is the essential guide for parents, families, and educators committed to creating a world where transgender and nonbinary youth can thrive. With compassionate insights, evidence-based research, and practical advice, this groundbreaking book provides the clarity and reassurance needed to navigate the complex journey of raising trans and gender-expansive children"--